2013
DOI: 10.1371/journal.pone.0062378
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations of Type 2 Diabetes with Islet Amyloid Polypeptide Processing and Degrading Pathways in Asian Populations

Abstract: Type 2 diabetes (T2D) is a complex disease characterized by beta cell dysfunctions. Islet amyloid polypeptide (IAPP) is highly conserved and co-secreted with insulin with over 40% of autopsy cases of T2D showing islet amyloid formation due to IAPP aggregation. Dysregulation in IAPP processing, stabilization and degradation can cause excessive oligomerization with beta cell toxicity. Previous studies examining genetic associations of pathways implicated in IAPP metabolism have yielded conflicting results due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The link between a family history of diabetes and elevated risk of Type 2 diabetes involves complex interactions of genes, common behaviours, shared environment and epigenetic modification [16]. In keeping with this, using probands with familial young-onset diabetes in our Chinese cohort, our group had identified novel risk loci associated with Type 2 diabetes [20][21][22][23][24]. In this connection, previous studies have demonstrated the influence of family history on the age of diagnosis [17].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The link between a family history of diabetes and elevated risk of Type 2 diabetes involves complex interactions of genes, common behaviours, shared environment and epigenetic modification [16]. In keeping with this, using probands with familial young-onset diabetes in our Chinese cohort, our group had identified novel risk loci associated with Type 2 diabetes [20][21][22][23][24]. In this connection, previous studies have demonstrated the influence of family history on the age of diagnosis [17].…”
Section: Discussionmentioning
confidence: 72%
“…People with young-onset diabetes are more likely to carry susceptibility genes that put them at higher risk of developing diabetes at an earlier age compared with their older counterparts [17,19]. In keeping with this, using probands with familial young-onset diabetes in our Chinese cohort, our group had identified novel risk loci associated with Type 2 diabetes [20][21][22][23][24]. Most of these variants had been replicated in other Asian populations although the effect size was reduced in more heterogeneous populations.…”
Section: Family History Of Young-onset Versus Late-onset Diabetes Andmentioning
confidence: 99%
“…• This finding also contributes to the growing body of knowledge aimed at unraveling the intricacies of protein-protein interactions and provides a foundation for future research endeavors in the development of targeted therapeutics for metabolic disorders, particularly diabetes (T2DM) and obesity [57,58].…”
Section: Discussionmentioning
confidence: 72%
“…2. This finding also contributes to the growing body of knowledge aimed at unraveling the intricacies of protein-protein interactions and provides a foundation for future research endeavors in the development of targeted therapeutics for metabolic disorders, particularly diabetes (T2DM) and obesity [57,58]. 3.…”
Section: Discussionmentioning
confidence: 81%